2019
DOI: 10.18517/ijaseit.9.1.2739
|View full text |Cite
|
Sign up to set email alerts
|

IT Risk Identification and Evaluation: a Case Study on XYZ University

Abstract: The purpose of this paper is to demonstrate that Failure Mode Effect Analysis (FMEA) can be applied to the educational field to identify various failure modes and its potential failure effect that could occur in anytime. FMEA is widely used in a design, a manufacturing or assembly process, or a product and service for identifying all possible failures. Risk identification is part of risk management. Therefore it is a critical first step of it. This paper is a case study on XYZ University which trying to implem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
3
0
1
Order By: Relevance
“…The results of the study showed that for the majority of respondents, the transition to distance learning did not become a deep problem, given the high involvement of young people in online communication systems, the presence of most modern devices from which to study (Albertivan, et al, 2019;Sansone & Bortolotti, 2021). Of the technological component, the most problematic was not the development of learning platforms, but the stability of Internet connections, because the Internet speed varies from one territory to another.…”
Section: Discussionmentioning
confidence: 96%
“…The results of the study showed that for the majority of respondents, the transition to distance learning did not become a deep problem, given the high involvement of young people in online communication systems, the presence of most modern devices from which to study (Albertivan, et al, 2019;Sansone & Bortolotti, 2021). Of the technological component, the most problematic was not the development of learning platforms, but the stability of Internet connections, because the Internet speed varies from one territory to another.…”
Section: Discussionmentioning
confidence: 96%
“…The fourth step is to measure supply chain disruptions using the Failure Mode and Effects Analysis (FMEA) approach. This stage measures the failure rate (Severity-S), the probability of occurrence (Occurance-O), and the failure detection rate (Detection-D) (Albertivan et al, 2019). The fifth step is to analyze the impact of dis- ruption on time, quality, and cost based on a user questionnaire.…”
Section: Research Stagesmentioning
confidence: 99%
“…Os sistemas de apoio à decisão (SAD) são amplamente utilizados para avaliação de risco em TI [4], [6], [7], [8], pois tomadas de decisões nesse contexto são fatores que estão associados as consequências positivas e negativas. Logo, a atenção para construção de um modelo de avaliação de desempenho possibilita um gerenciamento eficaz desses riscos, abordando variáveis do processo, na qual propõe realizar um aperfeiçoamento contínuo, incluindo estratégias para os gestores realizarem suas tomadas de decisão [9], [10], [11] atendendo como um modelo de apoio a decisão.…”
Section: Introductionunclassified